Preparation and properties of antibacterial PVDF composite thin films. (5th November 2021) - Wang, Andong; Shao, Mingwei; Yang, Fan; Shao, Chenkang; Chen, Caifeng
Graphical abstract: Highlights: 3D printing of PVDF/TPs film with high β-phase and crystallinity. PVDF/TPs thin films with porous structure and hydrophobicity. Silver ions are easily deposited on the PVDF/TPs surface with porous structure. The E. coli inhibition rate of the PVDF/TPs/Ag composite thin film is 99.58%. Abstract: As medical dressings, polyvinylidene fluoride (PVDF) thin films loaded with antimicrobial agents offer excellent wound infection control. In this study, PVDF/tea polyphenol (TPs) and PVDF/TPs/Ag composite thin films were prepared by electrically assisted three-dimensional (3D) printing method. The surface morphology, hydrophilicity, and antibacterial properties of the composite thin films were studied. The results showed that the presence of appropriate amount of TPs promoted the crystallinity and β-phase content of the PVDF thin films, and TPs played an important role in the formation of abundant holes on the surface of PVDF films. It facilitated the deposition of silver nanoparticles on the surface of PVDF thin film and improved the uniformity of their distribution. The Escherichia coli ( E. coli ) inhibition rate of the PVDF/TPs composite thin film reached 97.22%. The antibacterial activity of this composite thin film improved significantly after the deposition of silver nanoparticles, and the E. coli inhibition rate of the PVDF/TPs/Ag composite thin film was 99.58%.